Learning model experimentation Think Talk Write with project learning against mathematics learning outcomes - Nur Amalafitra; Anwas Mashuri; Budi Sasomo (Universitas Sarjanawiyata Tamansiswa, 2023)
This research was conducted with the aim of seeing which model is better between the TTW learning model and Project learning, TTW, and direct learning of students' mathematics learning outcomes in the matter of comparison of values ​​and comparisons of turning values ​​in class VII SMPN 2 Jogorogo. With a total of 68 students for the experimental group and 34 for the control group. Quasi Experimental Design is the type of research used in this study with the sampling technique that is Cluster Random Sampling. In this study, the sample consisted of three groups with normal and homogeneous distribution. Experimental group I (VII A) was given the TTW learning model with Project learning, Experimental group II (VII B) was given the TTW learning model, while the control group (VII C) was given a direct learning model. Hypothesis testing was carried out by a one way anova test and post-anova follow-up test. The conclusions that can be drawn from this study are (1) Obtained differences in TTW mathematics learning outcomes with Project learning get an average of 78.24, TTW got an average of 71.03, and direct learning get an average of 63.24 with the conclusion Fobs (13,13) ˃ Ftable (3.09). (2) The TTW learning model with Project learning gives results that are as good as the TTW, seen from Fobs (6,06) ˂ Ftable (6,18). (3) The TTW learning model with Project learning gives better results than direct learning, seen from Fobs (26,25) ˃ Ftable (6,18). (4) The TTW learning model gives better results than direct learning, seen from Fobs (7,08) ˃ Ftable (6,18).